Investigating the role of government trade policies and regulations on smuggling cosmetic products - Sahar Seifpoor; Reza Agha Mousa (Management Science Letters)
This paper investigates the effects of government trade policies as well as the rules and regulations on smuggling cosmetic products in Iran. The study considers the effects of five important factors including high tariffs and bureaucratic procedures, registration process, size and expire date, lack of accurate monitoring of distribution channels and government recent regulation failure on growth of smuggling cosmetic products in Iran. The proposed study uses structural equation modeling to examine the effects of these five components. The results indicate a positive and meaningful relationships between four variables including registration process (β = 0.84, P-value = 0.000), size and expire date (β = 0.86, P-value = 0.000), high rate of tariff (β = 0.88, P-value = 0.000) and government recent regulation failure (β = 0.97, P-value = 0.000) on growth of smuggling cosmetic products in Iran. In addition, the study has detected a negative and meaningful relationship between lack of accurate monitoring of distribution channels and growth of smuggling cosmetic products in Iran (β = -0.18, P-value = 0.000).